The Shape of Corneal Deformation Alters Air Puff–Induced Loading - Yousefi, Atieh; Roberts, Cynthia J.; Reilly, Matthew A. (Frontiers in Bioengineering and Biotechnology, 2022)
Purpose: To determine the dynamic modification of the load exerted on the eye during air-puff testing by accounting for deformation of the cornea. Methods: The effect of corneal load alteration with surface shape (CLASS) was characterized as an additional component of the load produced during the concave phase where fluid outflow tangential to the corneal surface creates backward pressure. Concave phase duration (tCD), maximum CLASS value (CLASSmax), and the area under CLASS-time curve (CLASSint) are calculated for 26 keratoconic (KCN), 102 normal (NRL), and 29 ocular hypertensive (OHT) subjects. Tukey’s HSD tests were performed to compare the three subject groups. A p-value of less than .05 was considered statistically significant. Results: Accounting for CLASS increased the load by 34.6%±7.7% at maximum concavity. These differences were greater in KCN subjects (P<0.0001) and lower in OHT subjects (P=0.0028) compared to NRL subjects. tCD and CLASSint were significantly longer and larger, respectively for KCN subjects in comparison with the NRL and OHT groups (P<0.0001). Conclusion: Load characterization is an essential step in assessing the cornea’s biomechanical response to air-puff-induced deformation. The dynamic changes in corneal surface shape significantly alter the load experienced by the corneal apex. This implies a subject-specific loading dynamic even if the air-puff itself is identical. This is important when comparing the same eye after a surgical procedure or topical medication that alters corneal properties. Stiffer corneas are least sensitive to a change in load, while more compliant corneas show higher sensitivity.